Towards an explanatory model for challenging behaviour in person with intellectual disabilities in the Capricorn District, Limpopo Province - Lekota, Tebogo (My University, 2020)
Persons living with intellectual disabilities (ID) at times display behaviours that are a challenge for healthcare professionals, parents and teachers. These challenging behaviours are often presented in health-care, educational, or social care services by individuals with intellectual disabilities. However, what could be explained as challenging may be understood differently through cultures, beliefs or surroundings. The aim of the study was to conceptualise and develop an explanatory model for challenging behaviour in persons with intellectual disabilities. The study comprised twenty (23) participants who were parents and teachers of persons with intellectual disability. The target population of the study live in Ga-Dikgale and Ga-Molepo villages that are located in the Capricorn District, Limpopo Province. These villages were chosen because they have special schools for children with ID. A semi-structured, in-depth, one-on-one interview was used to collect data. The data was analysed using thematic content analysis (TCA). Three superordinate themes emerged that covered the understanding of challenging behaviour from the participants. These themes were: (a) knowledge about challenging behaviour; (b) beliefs about causal explanations of challenging behaviour; and, (c) coping with challenging behaviour. The results revealed that participants held varied beliefs regarding causal explanations of challenging behaviour. Cultural background of the participant seemed to play a critical role in shaping these beliefs. Additionally, three modes of coping were used by the participants in the study to cope with challenging behaviour. These are: cultural/traditional coping; religious coping; and, family and professional support methods. A Bio-Psycho-Socio-Cultural Model (BPS-C) was subsequently developed to explain challenging behaviour of persons with intellectual disability. This model integrates components of the Bio-Psycho-Social model (biological characteristics, behavioural factors, and social condition such as social support and family relationships) and cultural aspects to conceptualise challenging behaviour as understood and explained by parents and teachers of persons with intellectual disability.
Thesis (Ph.D. (Psychology)) -- University of Limpopo, 2021
Keywords: Persons living with intellectual diabilities; Health care professionals; Parents and teachers; Challenging behaviours; Intellectual disability -- Diagnosis; Intellectual disability -- South Africa; Behavioral assessment -- South Africa